Photoperiodic Changes in Both Hypothalamus Neurotransmitters and Circulating Gonadal Steroids Metabolomic Profiles in Relation to Seasonal Reproduction in Male Quail - Xu, Yanglong; Jiang, Danli; Liu, Jiaxin; Fu, Yuting; Song, Yan; Fan, Di; Huang, Xuefei; Liufu, Sui; Pan, Jianqiu; Ouyang, Hongjia; Tian, Yunbo; Shen, Xu; et al. (Frontiers in Physiology, 2022)
Both hypothalamic neurotransmitters and serum steroid hormones are impacted by photoperiod and have effects on physiology and seasonal reproductive. However, the relationship between circulating gonadal steroids and hypothalamic neurotransmitters underlying different photoperiod is still unclear. To further understand the crosstalk of neurotransmitters and steroids in seasonal reproduction, metabolic changes of 27 neurotransmitters concentrated in hypothalamus tissues and 42 steroids hormones in serum were assessed during two artificial photoperiodic programs. The results showed that photoperiod induce testicular atrophy and recrudescence. In L-to-S groups , significantly decreased levels of testosterone concentration were found in serum (P < 0.001) and increased 11-Dehydrocorticosterone (P < 0.05); Testosterone were almost undetectable at SD_14d. In addition, the hypothalamus exhibited significantly increased arginine and 4-aminobutyric acid (GABA) concentration and decreased serotonin and epinephrine content (P < 0.01 or P < 0.05). Accordingly, serum testosterone and androstenedione became detectable at LD_3d in the S-to-L group and were markedly increase at LD_7d. Furthermore, Serum androstenedione showed a significant increase with long light expose (P < 0.01). Additionally, the hypothalamus exhibited both significantly increased L.tryptophan and phenylalanine concentration, as well as decreased L-glutamine and L-glutamine.acid content (P < 0.01 or P < 0.05). Serotonin metabolism showed significant differences between L-to-S group and S-to-L group. Furthermore, In the correlation analysis, serum testosterone .had a positive correlation with 5-Hydroxyindole-3-acetic acid (5-HIAA), while Androstenedione was significantly negative with L.Tryptophan in L-to-S (P < 0.05). However, in S-to-L group, serum testosterone showed strong negative correlation with both serotonin and 5-HIAA (P < 0.05), but positive correlation with L.Tryptophan (P < 0.01), while Androstenedione was significantly negative correlation with both serotonin (P < 0.05) and L-Glutamine (P < 0.01). Photoperiod also had significant effects on the mRNA expression. We found significant differences in gene expression patterns of both serotonin signaling and steroid biosynthesis, while MAOB, NR5A1 and 3β-HSD showed an opposite tendency between two groups. Taken together, our results revealed that circulating gonadal steroids and hypothalamic neurotransmitters were significantly impact quail’s seasonal reproduction. Circulating gonadal steroids have different effects on neurotransmitter at different photoperiodism, which may coordinately influence the seasonal reproduction of quails.